Mengungkap Teori dan Pratik Pendekatan Cognitive Behavioral Therapy (CBT) dalam Konseling Islam - Mawadah, Khisna; Irsyadunnas, Irsyadunnas (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2025)
The Cognitive Behavioral Therapy (CBT) approach has been proven effective in helping individuals overcome various psychological issues. In the context of Islamic counseling, integrating CBT with Islamic values offers a holistic solution that addresses both psychological and spiritual aspects of clients. This approach employs cognitive restructuring and behavioral modification techniques combined with Islamic principles such as muhasabah (self-reflection), tawakkal (trust in God), and worship practices. This study demonstrates that the application of Islam-based CBT enhances counseling effectiveness, particularly for Muslim clients, as it aligns with their cultural and religious beliefs. However, the success of this approach relies on counselors proficient in both aspects. With the development of a more structured Islamic CBT counseling model and increased public awareness, this approach holds significant potential for broader implementation.